THE EFFECT OF TEACHER'S ACCURACY IN IMPLEMENTING LEARNING IMPLEMENTATION PLANS (RPP) ON STUDENTS' LEARNING OUTCOMES IN AQIDAH AHLAK SUBJECT AT MAN - M. Dahlan Rabbanie; Fitri Widyasari; Kholil Nawawi (Universitas Labuhanbatu, 2023)
Aqidah Akhlak material is one of the materials taught at MAN which contains divinity and attitudes. This material is very important to be taught to students so that they can know their God and be able to interact well with humans. Because of the importance of Aqeedah Akhlak material in MAN, it is expected that teachers can teach well and in accordance with the lesson plans that have been made. The purpose of this study was to determine the effect of the teacher's accuracy in carrying out the learning implementation plan on student learning outcomes in the Aqeedah Akhlak subject at MAN. The method used is a quantitative method with a field study approach. The total population in this study was 275 students with a sample of 159 students in class X MIPA at MAN who were determined using probability techniques with simple random sampling. The data collection technique uses a questionnaire developed in 30 statements. The results of calculating the validity test for both variables show that r count> 0.155. This research instrument has a reliability of 0.900 for the X variable and 0.838 for the Y variable. Furthermore, the data normality test results are 0.200. Meanwhile, the homogeneity test obtained a result of 0.181. The results showed that the teacher's accuracy in implementing the learning implementation plan had an influence on student learning outcomes as evidenced by the results of data analysis of 0.706 with a determination value of 0.499 or 49.9%.Keywords: Aqidah Akhlak; Learning outcomes; Teacher's AccuracyAbstrak Materi aqidah akhlak adalah salah satu materi yang diajarkan di MAN yang berisi tentang ketuhanan dan sikap perilaku. Materi ini sangat penting untuk diajarkan pada peserta didik agar mereka bisa mengenal Tuhannya dan mampu berinteraksi dengan baik terhadap manusia. Karena pentingnya materi aqidah akhlak di MAN, maka diharapkan guru dapat mengajar dengan baik dan sesuai dengan rencana pelaksanaan pembelajaran yang telah dibuat. Tujuan penelitian ini untuk mengetahui pengaruh ketepatan guru dalam melaksanakan rencana pelaksanaan pembelajaran terhadap hasil belajar peserta didik pada mata pelajaran aqidah akhlak di MAN. Metode yang digunakan adalah metode kuantitatif dengan pendekatan studi lapangan. Jumlah populasi dalam penelitian ini adalah 275 orang peserta didik dengan sampel sebanyak 159 orang peserta didik kelas X MIPA di MAN yang ditentukan menggunakan teknik probabilitas dengan simple random sampling. Teknik pengumpulan data menggunakan angket yang dikembangkan dalam 30 pernyataan. Hasil perhitungan uji validitas untuk kedua variabel menunjukkan bahwa yaitu r hitung > 0,155. Instrument penelitian ini memiliki reliabilitas sebesar 0,900 untuk variabel X dan 0,838 untuk variabel Y. Selanjutnya untuk hasil uji normalitas data sebesar 0,200. Sedangkan, uji homogenitas memperoleh hasil sebesar 0,181. Hasil penelitian menunjukkan bahwa ketepatan guru dalam melaksanakan rencana pelaksanaan pembelajaran memberikan pengaruh terhadap hasil belajar peserta didik terbukti dari hasil analisis data sebesar 0,706 dengan nilai determinasi sebesar 0,499 atau 49,9%.Kata Kunci: Aqidah Akhlak; Hasil Belajar; Ketepatan Guru